2020
DOI: 10.1186/s13395-020-00245-2
|View full text |Cite
|
Sign up to set email alerts
|

Exercise enhances mitochondrial fission and mitophagy to improve myopathy following critical limb ischemia in elderly mice via the PGC1a/FNDC5/irisin pathway

Abstract: Background Elderly populations are susceptible to critical limb ischemia (CLI), but conventional treatments cannot significantly decrease amputation and mortality. Although exercise is an effective “non-pharmacological medicine” targeting mitochondria to improve skeletal muscle function, few studies have focused on the application of exercise in CLI. Methods Elderly male C57BL/6 mice (14 months old) were used to establish a CLI model to assess the effect of exercise on perfusion, performance recovery, apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…PINK1 and Parkin expression could significantly decrease in the Irisin/FNDC5 knockout mice and accompanied with mitochondrial dysfunction in myocardium [ 38 , 39 ], which suggested that irisin/FNDC5 was positively correlated with PINK1 and Parkin expression. Our present study provided direct evidence for exercise induced up-regulated expression of Irisin and enhanced PINK1/Parkin-mediated mitophagy in the myocardium, which was consistent with the results of previous studies [ 40 , 41 , 42 ]. Our study also presented that resistance exercise group had better effect in different types of exercise and skeletal muscle electrical stimulation intervention.…”
Section: Discussionsupporting
confidence: 93%
“…PINK1 and Parkin expression could significantly decrease in the Irisin/FNDC5 knockout mice and accompanied with mitochondrial dysfunction in myocardium [ 38 , 39 ], which suggested that irisin/FNDC5 was positively correlated with PINK1 and Parkin expression. Our present study provided direct evidence for exercise induced up-regulated expression of Irisin and enhanced PINK1/Parkin-mediated mitophagy in the myocardium, which was consistent with the results of previous studies [ 40 , 41 , 42 ]. Our study also presented that resistance exercise group had better effect in different types of exercise and skeletal muscle electrical stimulation intervention.…”
Section: Discussionsupporting
confidence: 93%
“…PGC1α in muscle is reported to stimulate an increase in FNDC5 expression in vitro and in vivo ( Bostrom et al, 2012 ). A recent study indicates that exercise increases mitochondrial fission and selective autophagy by PGC1a/FNDC5/irisin pathway, and promotes recovery of ischemic muscle ( He et al, 2020 ). These studies suggest that irisin may play an important role in exercise relieving skeletal muscle atrophy, thereby maintaining bone load and bone mass.…”
Section: Role Of Exercise In Regulating Bone Metabolismmentioning
confidence: 99%
“…Exercise is a well-established lifestyle modification that retards aging and increases human healthspan [ 283 ]. Exercise enhances mitophagy and autophagy [ 284 , 285 ], which are associated with the inhibition of mPTP. It was shown that exercise training decreases susceptibility to Ca 2+ -induced mPTP opening in heart mitochondria [ 286 ].…”
Section: Lifespan and Healthspan Extension Paradigms And Mptpmentioning
confidence: 99%